Liver Angiosarcoma: Rare tumour associated with a poor prognosis, literature review and case report (2016)
We report a case of minimally invasive nephrectomy of a kidney transplanted into the abdominal cavity in a child. A 15-year-old girl underwent transplantation with a cadaveric donor kidney due to congenital pyelonephritis, vesicoureteral reflux, and secondary bladder atrophy. The transplant was complicated by hyperacute rejection, cytomegalovirus infection, and anastomotic stenosis of the Bricker neobladder. After recurrent urinary tract infections, the patient was reintroduced to hemodialysis in 2010. After pneumo-peritoneum, we placed 2 10-mm trocars in the hypochondrium and left side and 2 5-mm in the left iliac fossa and right upper quadrant